2010
DOI: 10.1002/hbm.21119
|View full text |Cite
|
Sign up to set email alerts
|

Effective connectivity of the multiplication network: A functional MRI and multivariate granger causality mapping study

Abstract: Developmental neuropsychology and functional neuroimaging evidence indicates that simple and complex mental calculation is subserved by a fronto-parietal network. However, the effective connectivity (connection direction and strength) among regions within the fronto-parietal network is still unexplored. Combining event-related fMRI and multivariate Granger Causality Mapping (GCM), we administered a multiplication verification task to healthy participants asking them to solve single and double-digit multiplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 83 publications
1
45
1
1
Order By: Relevance
“…Here we showed that in both groups, delta connectivity was greater during mental calculation than in resting state, a finding in line with the previous literature. This increased connectivity between the left and right anterior regions indicates the necessity of the interaction between both hemispheres for the performance of mental calculation and could be engaged in updating of arithmetic operations and manipulation of information (Krueger et al 2011).…”
Section: Resting Vs Idics Taskmentioning
confidence: 96%
See 1 more Smart Citation
“…Here we showed that in both groups, delta connectivity was greater during mental calculation than in resting state, a finding in line with the previous literature. This increased connectivity between the left and right anterior regions indicates the necessity of the interaction between both hemispheres for the performance of mental calculation and could be engaged in updating of arithmetic operations and manipulation of information (Krueger et al 2011).…”
Section: Resting Vs Idics Taskmentioning
confidence: 96%
“…Conversely, there was a broad desynchronization in both groups in the IDICS task compared to resting state. This may reflect the activation of areas needed for calculation-such as the frontoparietal network (Krueger et al 2011)-or the deactivation of others that are able to adapt to the cognitive difficulty. Each factor could play a role in the successful execution of cognitive tasks.…”
Section: Resting Vs Idics Taskmentioning
confidence: 99%
“…This method is implemented using a multivariate autoregressive (MVAR) model. Several earlier studies have used these MVAR models based on the GC framework to study the predictive relationship between time series from different brain regions (Abler et al, 2006;Deshpande et al, 2011;Krueger et al, 2011;Lacey et al, 2011;Roebroeck et al, 2005).…”
mentioning
confidence: 99%
“…Authors reported that first-order and higher-order quantifiers both recruit right inferior parietal cortex, suggesting that a numerosity component contributes to quantifier comprehension. In fact, parietal activation was also widely reported in subjects asked to perform a simple number processing tasks [20,21,22,23,24] or arithmetic tasks [ 11,25,26].…”
Section: Discussionmentioning
confidence: 87%